A brighter future? The impact of insurance and socioeconomic status on cancer outcomes in the USA: a review. (June 2016) - Grant, Stephen R; Walker, Gary V; Guadagnolo, B Ashleigh; Koshy, Matthew; Mahmood, Usama
Uninsured and Medicaid-insured cancer patients have been shown to present with more advanced disease, less often receive cancer-directed therapy and suffer higher rates of mortality than those with private insurance. The Patient Protection and Affordable Care Act was signed into law in March of 2010 and seeks to increase rates of public and private health insurance. Although several provisions will in particular benefit those with chronic and high-cost medical conditions such as cancer, the extent to which disparities in cancer care will be eliminated is uncertain. Further legislative changes may be needed to ensure equal and adequate cancer care for all patients regardless of insurance or socioeconomic status.